The Influence of Organizational Culture on Employee Satisfaction and Loyalty at PT. Sarana the Future of Banggai - Susanto H. Pakaya; Nanin Hendarti Lasadam; Sri Desiyani Benda; Sutrisno K Djawa (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to analyze the influence of organizational culture, work motivation, and job satisfaction on employee loyalty in an organization. The results of the study indicate that organizational culture has a positive and significant influence on job satisfaction (O = 0.200; T-Statistics = 1.377; P-Value = 0.004) and employee loyalty (O = 0.351; T-Statistics = 3.141; P-Value = 0.002). In addition, work motivation is also proven to have a positive and significant influence on job satisfaction (O = 0.754; T-Statistics = 5.218; P-Value = 0.000) and employee loyalty (O = 0.355; T-Statistics = 2.682; P-Value = 0.008). Job satisfaction has a positive effect on employee loyalty (O = 0.284; T-Statistics = 3.675; P-Value = 0.000). However, job satisfaction does not significantly moderate the relationship between work motivation and employee loyalty (O = -0.084; T-Statistics = 0.778; P-Value = 0.437) or the relationship between organizational culture and employee loyalty (O = 0.147; T-Statistics = 1.337; P-Value = 0.182). These findings provide important managerial implications for organizations in improving employee satisfaction and loyalty through strengthening organizational culture and work motivation enhancement strategies. Thus, companies can improve employee engagement and retention in the long term.